A perspective on marriages and civil unions in South Africa Part 2 – Civil unions - Coertzen, Pieter (Stellenbosch Theological Journal, 2016)
The article argues that churches/religions ought to fully accept homosexuals as full members with all the rights that go with that, and treat them with Christian love, compassion and respect. But it also argues that if homosexual members do not abide by the official viewpoints of the Church and do not comply with the church’s requirements for membership and thereby threatens the faith identity of a church or a religion, church’s and religions have the right to terminate the membership of such members. Church’s and religions have a right to their faith viewpoint, to express that viewpoint and to expect from all their members to accept that viewpoint if they want to remain members of that church/religion. Just as churches and religions should show love and respect to homosexual members they can also expect from the homosexual members and outside pressure groups to respect the faith convictions of the church that the practising of homosexuality is in contradiction with what Scripture teaches in 1 Corinthians 6:9 and in many other parts of Scripture.